The Comparison of the Health Tourism Potentials of Metropolitan Cities in Turkey Using CRITIC and WASPAS Methods - Çubuk, Muhammed (Bingol University, 2022)
Diversification of incomes is an important element in economic and social development efforts. Health tourism, which has an important place in this diversity, has started to be discussed more, especially after the COVID-19 pandemic. Therefore, it has become a necessity for countries to develop diversity in alternative tourism services. In this context, in this study, which focuses on comparing the health tourism potentials of metropolitan cities in Turkey, comparison criteria were determined, and the weighting of these criteria was made with CRITIC, one of the multi-criteria decision-making methods. Thirty metropolitan cities were ranked by WASPAS method using these weights and criterion values. According to the ranking results, Istanbul, Antalya, Ankara, Izmir and Adana took the first five places. Hatay, Mersin, Mardin, Sakarya and Şanlıurfa took the last place. According to these results, strategic suggestions that are considered to contribute to regional and national competitiveness in the field of medical health tourism are also included.

Ekonomik ve sosyal kalkınma çabalarında gelirlerin çeşitlendirilmesi önemli bir unsurdur. Bu çeşitlilikte önemli bir konumda olan sağlık turizmi, özellikle COVID-19 pandemisinin ardından, daha fazla tartışılmaya başlanmıştır. Bu sebeple ülkelerin alternatif turizm hizmetlerinde çeşitlilik geliştirmeleri de bu doğrultuda zorunluluk haline gelmiştir. Bu kapsamda, Türkiye’de büyükşehirlerin sağlık turizmi potansiyellerini karşılaştırmaya odaklanan bu çalışmada karşılaştırma kriterleri belirlenmiş ve bu kriterlerin ağırlıklandırılması çok kriterli karar verme yöntemlerinden CRITIC ile yapılmıştır. Elde edilen bu ağırlıklar ve kriter değerleri kullanılarak, 30 büyükşehir WASPAS yöntemi ile sıralanmıştır. Sıralama sonuçlarına göre İstanbul, Antalya, Ankara, İzmir ve Adana ilk beş sırada yer almıştır. Son sıralarda ise Hatay, Mersin, Mardin, Sakarya ve Şanlıurfa yer almıştır. Bu sonuçlara göre sağlık turizmi alanında bölgesel ve ulusal ölçekte rekabetçiliğe katkı sağlayacağı değerlendirilen stratejik önerilere de yer verilmiştir.
Türkiye’de Büyükşehirlerin Sağlık Turizmi Potansiyellerinin CRITIC ve WASPAS Yöntemleri ile Karşılaştırılması
Keywords: Business Administration; İşletme